INTRODUCTION TO CULTURAL LITERACY AND CONFLICT PREVENTION IN INDONESIA: PENGENALAN LITERASI BUDAYA DAN PENCEGAHAN KONFLIK DI INDONESIA - Vidya Kusumawardani; Dinar Ayu Chandra Agustin; Riong Seulina; Danang Trijayanto; Sugeng Wahyudi (KHIDMATUNA: Jurnal Pengabdian Masyarakat, 2023)
This Community Service activity with the theme of cultural literacy was carried out on July 26 2022 with the title Introduction to Cultural Literacy and Conflict Prevention in Indonesia which was held at SMAN 40 Jakarta. The data collection method for outreach activities was carried out using quantitative data using a questionnaire using the Likert Scale approach consisting of SS, S, KS, TS, and STS during the pre-test and piost test which consisted of 10 questions. From the results of the pre-test data above, it can be concluded that of the 33 students, each of them already understands the importance of cultural literacy to prevent conflicts that occur in Indonesia which include question 1 (72%), question 2 (45%), question 3 (54%) ), question 4 (57%), question 5 (48%), question 6 (60%), question 7 (54%), question 8 (54%), question 9 (60%), and question 10 (78% ). Meanwhile, from the post test data, it can be concluded that of the 33 students, each of them already understands the importance of cultural literacy to prevent conflicts that occur in Indonesia which include question 1 (75%), question 2 (45%), question 3 (69%), question 4 (51%), question 5 (51%), question 6 (57%), question 7 (63%), question 8 (63%), question 9 (75%), and question 10 (72%). With an increase in students' understanding related to cultural literacy, this is in accordance with the program launched by the Ministry of Education and Culture which is to provide understanding to students related to attitudes to be able to respect each other, appreciate pluralism that exists in Indonesian society which is very vulnerable to racial conflicts.